The relationship between adaptive management of social-ecological syst ems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managi ng social-ecological systems involving high levels of complexity and u ncertainty. However, many obstacles still hamper its implementation. L aw is often seen as a barrier for moving adaptive management beyond th eory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this kno wledge gap by providing a systematic review of the peer-reviewed liter ature on the relationship between adaptive management and law in relat ion to social-ecological systems. We analyze how the scholarship defin es the concept of adaptive management, identifies the legal barriers t o adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geogr aphically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our re sults show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Le gal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation b ut also to make law itself more adaptive.